Analisis Penetapan Harga Jual dalam Etika Bisnis Islam di Konveksi Dinar Collection Desa Kedung Kebo Kecamatan Senori Kabupaten Tuban - Aprilisa, Anisa; Irawan, Agus Wahyu (Program Studi Ekonomi Syariah STAI Senori Tuban, 2023)
This research aims to find out how the selling price is determined at the dinar collection convection in Kedung Kebo village, Senori sub-district, Tuban regency. This research is field research using qualitative research with data sources coming from interviews, observation, and documentation. The analysis used in this research is the Miles and Huberman analysis model, including data reduction, data presentation, as well as conclusions and verification. Meanwhile, in checking the validity of the data, researchers used the triangulation method. The pricing applied in convection follows 4 principles: the principle of Oneness, the principle of Balance, the principle of Responsibility, and the principle of goodness. The pricing applied in the dinar collection convection is by taking profits that are not excessive and paying attention to the rights of consumers. The profit taken from all production processes is 10 percent. Of course, by taking profits, managers and consumers feel that they are both benefiting.